Petanque Aceh Athletes Achievement From 2015 to 2020 - Zahara; Riski, Arpin; Abdurrahman (Gladi : Jurnal Ilmu Keolahragaan, 2023)
Abstract Petanque is a new sport that originated in France. This game is played using an iron ball whose goal is to get the iron ball as close to the wooden ball as possible. Petanque has two basic techniques, namely shooting and pointing. Shooting is throwing the bored ball as precisely as possible on the target. Pointing is throwing a blank ball as close to a wooden ball as possible. The purpose of this study was to determine the achievements of Petanque Aceh athletes from 2015 to 2020. This study used a qualitative approach using descriptive historical methods. The subjects in this study totaled 18 people consisting of the head of the Aceh FOPI Pengprov, Aceh Petanque trainers, Petanque Sports observers and Aceh Petanque athletes. Data collection techniques in this study were used by means of interviews and data documentation. The data analysis technique in this study used a qualitative descriptive analysis. Based on the research results, it is known that the achievements of the Aceh Petanque Team have developed very well so that they are able to obtain achievements from year to year, from 2017 to 2020 the Aceh Petanque Team has participated in 16 National championships and 3 International championships, of the championships the Petanque team has participated in Aceh has collected a total of 57 medals, which are divided into 22 gold medals, 14 silver medals and 21 bronze medals. From these results it can be concluded that the achievements of the Petanque Aceh sport have developed very well so that they are able to carve out glorious achievements from year to year. Keywords: Achivement, Petanque, Athlete